Serologic evidence of HoBi-like virus circulation in Argentinean water buffalo - Pecora, Andrea (2017)
HoBi-like pestiviruses (also known as bovine viral diarrhea virus 3) have been sporadically reported from naturally infected cattle in Brazil, Asia, and Europe. Although HoBi-like viruses seem to be endemic in Brazilian cattle and buffalo, they have not been studied in the other countries of South America to our knowledge. Herein we report serologic results of buffalo from 12 large farms in Argentina located near the Brazilian border. These buffalo were not vaccinated against pestiviruses. Our results indicate that HoBi-like virus may be circulating in the northeastern region of Argentina given that half of the analyzed animals showed high levels of neutralizing antibodies against the pestivirus. The HoBi-like seropositive animals were also checked for neutralizing antibodies against BVDV-1a, BVDV-1b, and BVDV-2, and in most cases these animals had low levels or no detectable antibodies against these other pestiviruses. Our study suggests a need for continued pestivirus surveillance in Argentinean cattle and buffalo.